Settlement of the spiny lobster Panulirus in atus (Bouvier, 1895) postlarvae in the southeastern Gulf of California, Mexico - Valadez Manzano, Luis Miguel; Pérez-González, Raúl; Becerra-Arroyo, David; Ignacio-Borrego, Martín (Ecosistemas y Recursos Agropecuarios, 2017)
The settlement of Panulirus inflatus postlarvae in the southeastern Gulf of California was monitored approximately every week at one location (Puerto Viejo Bay) in Mazatlán Bay, from november 2009 to October 2010. Each sampling date was assigned to the lunar phase. Modi ed sandwich collectors were used to capture postlarval lobsters. Three collectors were used to examine pueruli settlement. A total of 238 P. inflatus pueruli were collected, which included 40 pueruli (17 %) and 198 post-pueruli (83 %). Settlement was highest using collector number one (140 pueruli), and november 2009 was the month with the greatest total number of animals (121). Signi cant di erences were found with respect to the lunar phase, but the higher settlement in this study occurred during the new moon phase.
Keywords: Gulf of California; Panulirus inflatus; Pueruli settlement; Modified sandwich collector